2019
DOI: 10.1097/pcc.0000000000002008
|View full text |Cite
|
Sign up to set email alerts
|

Specific Viral Etiologies Are Associated With Outcomes in Pediatric Acute Respiratory Distress Syndrome*

Abstract: Objectives: Infectious pneumonia is the most common cause of acute respiratory distress syndrome, with viruses frequently implicated as causative. However, the significance of viruses in pediatric acute respiratory distress syndrome is unknown. We aimed to characterize the epidemiology of viral pneumonia in pediatric acute respiratory distress syndrome and compare characteristics and outcomes between pneumonia subjects with and without viruses. Secondarily, we examined the association between speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
5
12
1
Order By: Relevance
“…Acute viral bronchiolitis and viral pneumonia are overlapping, and it is often difficult to differentiate between them, particularly in children under 2 years of age. Viruses were the identified pathogen in 92% of our patients, compared to 70% in a similar study reported by Roberts et al [ 5 ].…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Acute viral bronchiolitis and viral pneumonia are overlapping, and it is often difficult to differentiate between them, particularly in children under 2 years of age. Viruses were the identified pathogen in 92% of our patients, compared to 70% in a similar study reported by Roberts et al [ 5 ].…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, infections account for more than half of the cases of PARDS, particularly lower respiratory tract infections such as pneumonia and bronchiolitis, with viruses frequently implicated [ 3 ]. However, the importance of viral infections as a cause of PARDS in infants has not previously been described [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory infections leading to bronchiolitis or viral/bacterial pneumonia are the most common cause of admission to the PICU ( 1 ). Although some viruses, such as influenza A, are associated with worse outcomes, pediatric acute respiratory distress syndrome (PARDS) develops in patients from even mild viruses such as respiratory syncytial virus (RSV) ( 2 , 3 ). New respiratory viruses, such as severe acute respiratory syndrome coronavirus 2, are especially challenging as they may not be detected on first-pass testing.…”
mentioning
confidence: 99%
“…However, clinical measurement of BAL biomarkers has not become standard practice, possibly due to the heterogeneity of disease and host factors in adult ARDS. In contrast, PARDS may represent a more homogenous condition, as it is usually triggered by viral respiratory infections ( 2 ).…”
mentioning
confidence: 99%